"Active followers": An emerging role of information behaviour among group holiday makers. Issue 1 (18th October 2019) - Ye, Edwin Mouda; Du, Jia Tina; Ashman, Helen; Hansen, Preben; Huang, Songshan (Sam); Sigala, Marianna
ABSTRACT: In an era of information overload, people often work together on information‐intensive projects. Group holidaying is such an example where people plan and conduct trips together. In this poster paper we present preliminary findings from an ongoing investigation of collaborative information behaviour of group holidaymakers. Through a grounded‐theory approach, preliminary findings show that not all members of the travel group engage equally in the information search. A role labelled "active followers" is identified and the role‐taker's contribution to the group's information seeking and decision‐making is discussed. This paper calls for attention to heterogeneity within collaborating groups and invites further discussion of research into this topic in information science community.